Vacuolar Targeting and Characterization of Recombinant Antibodies - Ocampo, Carolina Gabriela (2018)
Plant-based platforms are extensively use for the expression of recombinant proteins, including monoclonal antibodies (mAbs). Generally, immunoglobulins (Igs) are sorted to the apoplast, which is often afflicted with intense proteolysis. Here, we describe methods to transiently express mAbs sorted to central vacuole in Nicotiana benthamiana leaves and to characterize the obtained IgG. Central vacuole is an appropriate compartment for the efficient production of Abs, consequently vacuolar sorting should be considered as an alternative strategy to obtain high protein yields.